Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/23780231231174823
|View full text |Cite
|
Sign up to set email alerts
|

Unsorted Significance: Examining Potential Pathways to Extreme Political Beliefs and Communities on Reddit

Abstract: Violent political extremists often point to online communities as motivating their behavior. However, researchers studying online exposure to extremism through structural mechanisms such as algorithms have not found strong evidence of their influence. At the same time, models of offline radicalization processes emphasize the importance of personal motivations, such as desire for significance and community, but do not fully account for online contexts. The authors integrate these approaches, which are both inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…motivating a recent headline-"Now Is the Time to Pay Attention to Trump's Violent Language" (Kingsbury 2023)it might be that a post's instructions (i.e., "go after") inspire a user to commit violence, but it could also be that a user is inspired by the fact that they read the words on a platform that symbolized a home community (e.g., Truth Social) or because of racial narratives evoked by the post's targets (i.e., New York's attorney general, who is a Black woman, and "shoplifters"). To offer another example, when Mann et al (2023) analyzed the pathways to extremism on Reddit, they observed that users valued certain fora because of other users' comments-the lexical component of content-as well as the names of the fora, such as "nonmainstream ideas, such as r/anarchism or r/libertarian," which intimated that users were "allowed to disagree with each other on certain points" (p. 7).…”
mentioning
confidence: 99%
“…motivating a recent headline-"Now Is the Time to Pay Attention to Trump's Violent Language" (Kingsbury 2023)it might be that a post's instructions (i.e., "go after") inspire a user to commit violence, but it could also be that a user is inspired by the fact that they read the words on a platform that symbolized a home community (e.g., Truth Social) or because of racial narratives evoked by the post's targets (i.e., New York's attorney general, who is a Black woman, and "shoplifters"). To offer another example, when Mann et al (2023) analyzed the pathways to extremism on Reddit, they observed that users valued certain fora because of other users' comments-the lexical component of content-as well as the names of the fora, such as "nonmainstream ideas, such as r/anarchism or r/libertarian," which intimated that users were "allowed to disagree with each other on certain points" (p. 7).…”
mentioning
confidence: 99%